2020
DOI: 10.1136/bmjopen-2019-032321
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of health after dietary changes in endometriosis: a qualitative interview study

Abstract: ObjectivesEndometriosis is a chronic disease with no known cure. Persons affected by this disease often use complementary therapies such as dietary changes to reduce their symptoms, and so it is important to investigate whether and how these therapies affect endometriosis symptoms. The aim of this study was to explore how persons with endometriosis experienced their health after dietary changes.DesignSemi-structured qualitative interviews were conducted with 12 persons with endometriosis who had made individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 58 publications
1
23
0
1
Order By: Relevance
“… - Intensity of headache, cystitis, muscular pain or fibromyalgia, irritable colon, dysmenorrhea, dyspareunia, chronic pelvic pain measured by VAS (0–100) before intervention and after 3 months—17b-estradiol—PGE2- CA-125 Significant reduction of the symptoms and the laboratory parameters in the first group - Difference in VAS score and laboratory parameters not presented; just the number of patients with VAS > 5 before and after the dietary intervention. No clear description of the inclusion-exclusion criteria—no description of the period of recruitment Vennberg Karlsson et al, 2020 [ 51 ] Sweden Qualitative interview study 12 - Individual, voluntary dietary changes Experiences of health after the dietary change reported during the interview Increase in well-being and a decrease in symptoms - Retrospective design—patient recruitment via endometriosis support forums—unclear dietary interventions—no objective measurement of pain symptoms …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… - Intensity of headache, cystitis, muscular pain or fibromyalgia, irritable colon, dysmenorrhea, dyspareunia, chronic pelvic pain measured by VAS (0–100) before intervention and after 3 months—17b-estradiol—PGE2- CA-125 Significant reduction of the symptoms and the laboratory parameters in the first group - Difference in VAS score and laboratory parameters not presented; just the number of patients with VAS > 5 before and after the dietary intervention. No clear description of the inclusion-exclusion criteria—no description of the period of recruitment Vennberg Karlsson et al, 2020 [ 51 ] Sweden Qualitative interview study 12 - Individual, voluntary dietary changes Experiences of health after the dietary change reported during the interview Increase in well-being and a decrease in symptoms - Retrospective design—patient recruitment via endometriosis support forums—unclear dietary interventions—no objective measurement of pain symptoms …”
Section: Resultsmentioning
confidence: 99%
“…Out of the nine human studies, two were randomized controlled trials [43,44], two prospective controlled studies [45,46], two prospective [47,48], and two retrospective [49,50] uncontrolled before-after studies and one qualitative study [51]. The follow-up period of studies ranged from 4 weeks to 12 months.…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, authors observed that most participants noted an impact from endometriosis-related fatigue on daily activities, social relationship, mood and emotion and working activities. In another study (Vennberg Karlsson et al, 2020 ), conducted on 12 persons with endometriosis, authors, through a semi-structured interview, analysed the experiences of health after dietary changes and observed that participants experienced an increase in well-being and a decrease in symptoms following their dietary and lifestyle changes. Differently, another study (Hållstam et al, 2018 ) analysed the women’s experience of painful endometriosis, observing that living with severe painful endometriosis signified a struggle for coherence.…”
Section: Introductionmentioning
confidence: 99%
“…However, although these studies were focalized to analyse the lived experiences of women with endometriosis, these studies analyzed only specific aspects of endometriosis such as fatigue (DiBenedetti et al, 2020 ), dietary changes (Vennberg Karlsson et al, 2020 ) or pain (Hållstam et al, 2018 ), while in our study, following the phenomenological methodology, we did not limit to analyse only one specific aspect, but the lived experiences in general. Knowing the lived experiences of women suffered by endometriosis, it is crucial to understand the physical and psychological implications that endometriosis could have on their lives, and consequently, give information to implement tailored intervention.…”
Section: Introductionmentioning
confidence: 99%